The Implicit Cultural Patterns in the Hamziya of Ibnu Khamis al-Tilimsani - Haimer, Malika (Journal of Human Sciences, 2023)
This article seeks to deal with one of the problems of cultural criticism by shedding light on the implicit cultural patterns in the Hamziya of Ibnu Khamis al-Tilmisani. This poem aesthetically expresses the author’s feelings but also includes various ideas and opinions with cultural dimensions that differ from the explicit content of the text. To achieve this aim, we ask the two following questions: What are the implicit cultural patterns in the Hamziya of Ibnu Khamis al-Tilimsani? What are its cultural dimensions? The paper attempts to shed light on the notion of pattern and that of implicit cultural pattern. This allows considering the interpretation of the cultural patterns in the text of al Hamziya. Underlying the text is the pattern known as nostalgia that is implicit in praise following a cultural view, which goes much beyond the explicit aspect in poetic discourse.